2012
DOI: 10.1080/07315724.2012.10720440
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 12-Week Lifestyle Intervention on Health Outcome and Serum Adipokines in Middle-Aged Korean Men with Borderline High Blood Pressure

Abstract: These results suggest that a short-term (12 weeks) lifestyle intervention had positive effects on blood pressure control and weight reduction in the subjects, but not on their blood levels of adipokines. It is interesting that blood level of baseline leptin was negatively associated with the changes in blood pressure after this short-term intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Surprisingly, except for serum leptin. Similar results were found by Kim et al (2012) for the same obesity parameters in fourteen men sample after 12 weeks of regular exercise. This confirms that altered adipokine level during aging is accompanied with significant changes in ob gene expression (Nogalska et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…Surprisingly, except for serum leptin. Similar results were found by Kim et al (2012) for the same obesity parameters in fourteen men sample after 12 weeks of regular exercise. This confirms that altered adipokine level during aging is accompanied with significant changes in ob gene expression (Nogalska et al, 2003).…”
Section: Discussionsupporting
confidence: 76%
“…(8) The study was published in English. To differentiate the effect of HIIT duration on cardiometabolic markers, a classification of ST-HIIT (<12 weeks) and LT-HIIT (≥12 weeks) based on previous studies20 29 30 was used in this review.…”
Section: Methodsmentioning
confidence: 99%
“…20 Considering the high sodium and low potassium intake in Korea, modifications of dietary patterns are a potential strategy for hypertension control. Previous Korean studies have demonstrated that dietary interventions that include both low-sodium and highpotassium diet reduced BP 21,22 ; however, the effects on BP could not be separated by either low-sodium or highpotassium intake. Although a few population-based Korean studies have investigated the association between dietary sodium and potassium intakes and BP, they did not consider the interaction between sodium and potassium.…”
mentioning
confidence: 99%